2005
DOI: 10.1093/jxb/eri319
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide is involved in abscisic acid-induced antioxidant activities in Stylosanthes guianensis

Abstract: Previous studies suggest that abscisic acid (ABA) stimulates the activities of antioxidant enzymes under normal and chilling temperature and enhanced chilling resistance in Stylosanthes guianensis. The objective of this study was to test whether nitric oxide (NO) is involved in the ABA-induced activities of the antioxidant enzymes in Stylosanthes guianensis due to its nature as a second messenger in stress responses. Plants were treated with NO donors, ABA, ABA in combination with NO scavengers or the nitric o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
188
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(201 citation statements)
references
References 34 publications
10
188
0
3
Order By: Relevance
“…In the previous studies reported that L-NNA decreases the activities of antioxidant enzymes and enhances lipid peroxidation (29). In accordance with previous studies, it was observed that 150 mg/kg dose of ISO induced a myocardial damage and significantly altered biochemical parameters and antioxidant enzyme activities in the present study (13).…”
Section: Discussionsupporting
confidence: 92%
“…In the previous studies reported that L-NNA decreases the activities of antioxidant enzymes and enhances lipid peroxidation (29). In accordance with previous studies, it was observed that 150 mg/kg dose of ISO induced a myocardial damage and significantly altered biochemical parameters and antioxidant enzyme activities in the present study (13).…”
Section: Discussionsupporting
confidence: 92%
“…6 and 7). NO has been suggested to increase the activities of antioxidant enzymes and up-regulate the expressions of the antioxidant genes in plants (Zhou et al, 2005;Zhang et al, 2007). It is well known that the antioxidant defense system plays vital roles in plants' tolerance to stressful conditions (Guan et al, 2009;Gill and Tuteja, 2010).…”
Section: No Involved In Spd-induced Chilling Tolerance In Tomatomentioning
confidence: 99%
“…Nitric oxide is effective in enhancing growth and development from seed germination to the adult stage (Desikan et al, 2004). It also promotes flowering and hormonal responses (Zhou et al, 2005). However, exogenous application of NO has been reported to enhance relative water content, chlorophyll, and proline contents of wheat plants under arsenic-induced oxidative stress (Hasanuzzaman et al, 2012).…”
Section: Introductionmentioning
confidence: 99%